Toward Multispecies Mourning: Imagining an Art Therapy for Ecological Grief. - Wharldall, Beatrice (Art Therapy: Journal of the American Art Therapy Association, 2024)
Witnessing the devastating impacts of climate change and species loss has left many of us grappling with inexpressible grief for our more-than-human world. The importance of creating therapeutic environments to facilitate ecological grieving is greater than ever. This article examines the potential benefits of art therapy in this context. These include: reducing the risk of disenfranchized grief through connection; containing and externalizing complexity; providing regulation; and empowering participants to continue engagement. Grief counseling frameworks offer solid foundations for future directions. However, First Nations perspectives provide richer understandings of our multispecies interdependencies, and will be central to forging collective and localized responses to ecological grief that build communities of healing—not just between cultures, but between species, too.